ACADEMICIAN SABIR KAMALOV: SCIENTIFIC-PEDAGOGICAL AND POLITICAL SCIENCE CAREER IN THE FIELD - Abatov, A.R. (SCIENCE and SOCIETY, 2026)
The article based on archival materials, extensively covers the activities of S.Kamalov in the political sphere. Using a specific example, his work as Deputy Chairman of the Supreme Council of Karakalpakstan and as a deputy of the Supreme Councils of Karakalpakstan and Uzbekistan for 40 years in 1959-1999 is highlighted. The scientific works of academician S.Kamalov and his achievements in political activity served as fundamental discoveries that have retained their significance in the historiography of our country.
Keywords: academician S.K.Kamalov; history; political activity; deputy; Central Asia; school; teacher; social activities